2015
DOI: 10.1590/0074-02760150222
|View full text |Cite
|
Sign up to set email alerts
|

DNA prime-protein boost based vaccination with a conserved region of leptospiral immunoglobulin-like A and B proteins enhances protection against leptospirosis

Abstract: Leptospirosis is a zoonotic disease caused by pathogenic spirochetes of theLeptospira genus. Vaccination with bacterins has severe limitations. Here, we evaluated the N-terminal region of the leptospiral immunoglobulin-like B protein (LigBrep) as a vaccine candidate against leptospirosis using immunisation strategies based on DNA prime-protein boost, DNA vaccine, and subunit vaccine. Upon challenge with a virulent strain ofLeptospira interrogans, the prime-boost and DNA vaccine approaches induced significant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…This indicated that L. interrogans Piscina may pose a risk to public health in the region ( Forster et al 2013 ). Due to its high virulence, this isolate has also been used as a challenge strain in experiments aimed to evaluate the protection afforded by novel recombinant vaccine candidates against leptospirosis in vaccinology laboratories ( Forster et al 2015 ).…”
mentioning
confidence: 99%
“…This indicated that L. interrogans Piscina may pose a risk to public health in the region ( Forster et al 2013 ). Due to its high virulence, this isolate has also been used as a challenge strain in experiments aimed to evaluate the protection afforded by novel recombinant vaccine candidates against leptospirosis in vaccinology laboratories ( Forster et al 2015 ).…”
mentioning
confidence: 99%
“…The level of the immune response induced by heterologous immunization is higher and more balanced than single immunization, and the protective effect is also improved. This strategy is expected to reduce the times of immunization compared with immunization with an inactivated vaccine alone, and theoretically, it can also improve the immunogenicity and long-term immune response induced by the vaccine [ 21 , 22 ], which warrants further experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The level of the immune response induced by heterologous immunization is higher, more balanced, and the protective effect is also improved. This idea is expected to reduce the times of immunization compared with immunizing an inactivated vaccine alone, and theoretically, it can also improve the immunogenicity and prolong the duration of the vaccine [20,21], which warrants later experiments.…”
Section: Discussionmentioning
confidence: 99%